Analysis of physics learning in elementary schools and the need for professional development: Is STEM education training necessary for elementary school teachers? - Didit Ardianto; Tustiyana Windiyani; Irma Rahma Suwarma; Karmilasari Karmilasari; Najla Nurul (Momentum: Physics Education Journal, 2024)
This study aims to explore pedagogical approaches and students’ engagement during STEM teaching. As many as 215 elementary school teachers in West Java were involved in this research. Those involved consisted of 161 women and 49 men. The majority of teachers have an elementary school teacher education background (87%), 7% have other educational backgrounds (Science Education/Mathematics Education/Social Education/Language Education), and the remaining 6% are in the sciences. The instrument used in this study was a closed questionnaire with 20 items from a Likert scale survey. The results of the study show that 50% of elementary school teachers very rarely use experimental approaches and problem-based learning when teaching STEM content. More than 60% of teachers also very rarely use the inquiry approach in teaching the four contents. The approach that is often used by teachers in teaching STEM is a collaborative and integrated approach. In addition, the survey results also show that more than 50% of students are very rarely involved in inquiry and engineering practice activities when learning about STEM content. The analysis of professional development needs showed that the majority of elementary school teachers have never received a professional development program regarding STEM education. In fact, the majority of teachers have a positive attitude towards the coaching program, which has an impact on increasing their competence. Apart from that, the results of this research also show that there is a lack of external support (from universities, educational practitioners, and researchers) for teachers in coaching programs. These findings provide evidence that teachers still need to receive training on pedagogical approaches that are relevant to integrated STEM education. The existence of training on STEM education is expected to improve the quality of STEM learning in the classroom. Thus, students' involvement in scientific and engineering practice when learning STEM becomes more dominant.